Identification of aberrant microRNA expression pattern in pediatric gliomas by microarray - Liu, Fatao (BioMed Central, 2013)
BACKGROUND: Brain tumor remains the leading cause of disease-related death in children. Many studies have focused on the complex biological process involved in pediatric brain tumors but little is know about the possible role of microRNAs in the genesis of these tumors. METHODS: In this study, we used a microRNA microarray assay to study the expression pattern of microRNAs in pediatric gliomas and matched normal tissues. RESULTS: We found 40 differentially expressed microRNAs, among which miR-1321, miR-513b, miR-769-3p were found be related to cancer genesis for the first time. The expression of selected microRNAs were then confirmed by qRT-PCR. Furthermore, GO and pathway analysis showed that the target genes of the 40 differentially expressed microRNAs were significantly enriched in nervous system-related and tumor-related biological processes and signaling pathways. Additionally, an apoptosis-related network of microRNA–mRNA interaction, representing the critical microRNAs and their targets, was constructed based on microRNA status. CONCLUSIONS: In the present study we identified the changed expression pattern of microRNAs in pediatric gliamas. Our study also provides a better understanding of pediatric brain tumor biology and may assist in the development of less toxic therapies and in the search for better markers for disease stratification. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1323049861105720